Entrepreneurship and digitalisation in EU: twinning insights through a panel threshold regression - Nicolescu, Ana-Cristina; Lobonț, Oana-Ramona; Vătavu, Sorana; Bozga, Emilia (Journal of Business Economics and Management, 2024)
The study methodologically employs, in a novel perspective, the panel threshold analysis, considering the time frame 2006–2020, to capture the relationship between new business density rate, as a proxy for entrepreneurship, and individuals’ digital inclusion, as a proxy for digitalisation in EU countries. Based on the human capital theory, the results indicated a strong single threshold effect between individuals’ digital inclusion and new business creation, confirming that entrepreneurship is influenced by the skills, knowledge, and experience of the entrepreneurs, including their education, training, and work history. For EU countries, individuals’ digital inclusion boosts business creation only after reaching a certain level. When separating the EU countries from the perspective of their Innovation Index performance, the threshold effect was statistically evidenced in all categories but with different values. The strongest positive influence from digitalisation towards entrepreneurship was visible in emerging countries, while the lowest was for countries classified as moderate innovators. The research provides an original framework for understanding the complex factors that drive entrepreneurship and can help researchers and practitioners develop strategies for promoting entrepreneurial activity. Digitalisation’s opportunities are significant, and entrepreneurial individuals and organisations able to adapt and innovate are more likely to be successful.